Entwicklung und vergleichende Bewertung einer bildbasierten Markierungslichtsteuerung für Kraftfahrzeuge - Hörter, Marko Heiko (Schriftenreihe / Institut für Mess- und Regelungstechnik, Karlsruher Institut für Technologie, 2013)
In automotive lighting technology there have been taken place intense research efforts in the field of adaptive lighting systems to provide a flexible luminance intensity distribution optimally adapted to the situational prevailing traffic and atmospheric situation in the last recent years.This paper describes the development and comparative evaluation of an image-based control system for a marking light approach designed for motor vehicles.